How do the terrorist influence young people? - El-Muhammady, Ahmad (2021)
The presentation addresses five basic questions related to terrorism: 1. Who is the terrorist? 2. What criteria used to determine terrorism? 3. How terrorist influences the youth? 4. What are the motives, push and pull factors, drivers to terrorism? 5. How to disengage youth or people from terrorism or violent extremism?